The Relationship Between Hand Grip and Pinch Strengths and Disease Activity, Articular Damage, Pain, and Disability in Patients with Rheumatoid Arthritis - Meryem DEDEOĞLU; Ümit GAFUROĞLU; Özlem YILMAZ; Hatice BODUR (Archives of Rheumatology, 2013)
Objectives: This study aims to investigate the relationship of hand grip and pinch strengths with disease activity, functional impairment, functional disability, articular damage, pain, and disease duration in patients with rheumatoid arthritis (RA). Patients and methods: Hand grip and pinch strength of 102 patients (78 females, 24 males; mean age 52.8±10.5 years; range 26 to 69 years) with RA were assessed using a dynamometer. The Disease Activity Score 28 joints (DAS 28), the Duruoz Hand Index (DHI), the Signals of Functional Impairment (SOFI) index, the Health Assessment Questionnaire (HAQ), the Rheumatoid Arthritis Articular Damage (RAAD) score, the Modified Sharp Score (MSS) and the visual analog scale (VAS) were used to analyze the possible relationship. Results: There was a statistically significant negative correlation between all grip and pinch strengths and the DAS 28 score, HAQ score, SOFI index, DHI, RAAD score, MSS, VAS, and disease duration (p<0.001). The DHI, SOFI index, and HAQ parameters were the most strongly correlated variables with hand strengths. The DHI, SOFI index, RAAD score, DAS 28 score, HAQ score, and MSS showed a statistically significant positive correlation with each other (p<0.001). The strongest correlation was between the HAQ and DHI (r=0.876; p<0.001). Conclusion: In this study, we found that hand grip and pinch strengths were negatively correlated with the disease activity, articular damage, pain, disease duration, functional impairment and disability in patients with RA. Our study results emphasize the importance of hand gripping and pinching abilities for the functional impairment and disability in patients with RA.